The utility of proximity-based herbicide exposure assessment in epidemiologic studies of Vietnam veterans (National Academies Press, 2008)
In past studies evaluating whether health problems experienced by Vietnam veterans might be linked to wartime use of Agent Orange or other herbicides, a fundamental challenge has been a lack of information about the veterans' level of exposure to these herbicides. To address that problem, researchers developed a model to assess the opportunity for herbicide exposure among these veterans. Using a geographic information system and a computerized database engine, the model makes it possible to link georeferenced data on herbicide spray paths with information about troop locations and calculate two different proximity-based exposure opportunity metrics. This report presents... guidance to the Dept. of Veterans Affairs about the best use of this herbicide exposure assessment model.